2009
DOI: 10.1021/ac901027f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Thermometers for Dual-Emission-Wavelength Measurements: Molecular Engineering and Application to Thermal Imaging in a Microsystem

Abstract: To facilitate thermal imaging, particularly in microdevices, one has to favor molecular thermometers in which the response is independent of the probe concentration and of the observation setup imperfections. Hence, this paper introduces two temperature fluorescent probes for ratiometric dual-emission-wavelength measurements in aqueous solutions. They are based on a nonathermal chemical reaction, either a conformational transition or a protonation, that induces a modification of their emission spectra as the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 75 publications
(138 reference statements)
1
78
0
Order By: Relevance
“…Differences in the electronic properties of each p-stacking and in the charge transfer process from a fluorescent probe, like, for instance, 2-aminopurine, result in marked changes in emission that can be readily monitored. Based on these results, Tashiro and Sugiyama have proposed a molecular nanothermometer and shown that fluorescence intensity correlates reproducibly with temperature in the range between 275 and 305 K. 161 Barilero et al 19 proposed a different approach using organic dyes as unimolecular fluorescent temperature probes for dualemission-wavelength measurements in aqueous solutions. The basic concept relies on a non-thermal chemical reaction (either a conformational transition or a protonation) inducing a modification of the dye emission spectra as the temperature changes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the electronic properties of each p-stacking and in the charge transfer process from a fluorescent probe, like, for instance, 2-aminopurine, result in marked changes in emission that can be readily monitored. Based on these results, Tashiro and Sugiyama have proposed a molecular nanothermometer and shown that fluorescence intensity correlates reproducibly with temperature in the range between 275 and 305 K. 161 Barilero et al 19 proposed a different approach using organic dyes as unimolecular fluorescent temperature probes for dualemission-wavelength measurements in aqueous solutions. The basic concept relies on a non-thermal chemical reaction (either a conformational transition or a protonation) inducing a modification of the dye emission spectra as the temperature changes.…”
mentioning
confidence: 99%
“…7). 19 The optical signal comes from the labelling of the beacon extremities by a pair of fluorophores engaged in FRET conferring appropriate photophysical properties for a ratiometric analysis. The authors describe a Fluorescein-Texas-Red donor-acceptor pair thermometer for the temperature interval 278-318 K with S m ¼ 4.5% K À1 at 295 K (Table 2 and Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first and fourth channels correspond to species simulating contaminants, the non-reactive NR sequence and the rapidly exchanging molecular beacon MB [5]. A star ( ) indicates an emitting fluorescent dye whereas a circle ( ) holds for a quenched one.…”
Section: Principlementioning
confidence: 99%
“…A star ( ) indicates an emitting fluorescent dye whereas a circle ( ) holds for a quenched one. To determine the thermal excitation phase and amplitude, we added to all the samples 2 μM of a Texas Red labeled molecular thermometer, MBr [4,5].…”
Section: Principlementioning
confidence: 99%